An Adaptive Robust Controller for Hydraulic Robotic Manipulators with a Flow-Mapping Compensator - Zhang, Fu; Zhang, Junhui; Xu, Bing; Zong, Huaizhi (International Journal of Fluid Power, 2021)
Proportional directional control valves have flexible control functions for the control of various hydraulic manipulators. It is foreseeable that the application of proportional directional control valves will be further expanded. However, due to its own structure, its important parameter, flow gain, is complex, and it has a complex functional relationship with valve opening and temperature. The variable flow gain reduces the performance of a strictly derived nonlinear controller. Therefore, it is necessary to consider the nonlinearity of flow gain in the controller design. In order to solve the above problems, this paper proposes an adaptive robust controller for a hydraulic manipulator with a flow-mapping compensator, which takes into account the nonlinear flow gain and improves the performance of the nonlinear controller. First, we established an adaptive robust controller of the hydraulic manipulator to obtain the load flow of the control input valve. Then, the function of flow gain, input voltage, and temperature are calibrated offline using cubic polynomial, and the flow-mapping compensator is obtained. Finally, we calculate the input voltage based on the flow-mapping compensator and load flow. The flow-mapping compensator further reduces the uncertainty of the model and improves the robustness of the system. By using the proposed controller, the control accuracy of the hydraulic manipulator is significantly improved.